Plainsong - Hosaka, Kazushi; Warham, Paul. (Champaign [Ill.] : Dalkey Archive Press, 2011)
'A nameless, ambitionless office worker finds his small apartment gradually invaded by three other people: all younger than himself, but seemingly no less adrift. The year is 1986, and the strange communal life of this foursome, extending over half a year, makes up the plot, such as it is, of Plainsong, as this ersatz family finds itself growing closer, and life continues--quietly--around them.'--P. [4] of cover.
Translated from the Japanese.
Keywords: Japanese fiction -- 20th century